PENGARUH MOTIVASI DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN KENDARAAN RODA DUA HONDA - NURUL HIDAYAH A RAHMAN; HARRY J. SUMAMPOUW; SOFIA A.P SAMBUL (Universitas Sam Ratulangi, 2016)
Abstract This research was based a decrease in sales of Honda motorcycles in the period 2011-2014. This sales decline shows a decrease in consumer buying decisions on Honda motorcycle products that can be formulated in this research that how consumers buying decision in the midst of motorcycle competition phenomenon becoming more strictly based on the consumer motivation, and consumer attitudes. The aim of the research is to influence of motivation and consumer attitudes toward buying decision of the Honda motorcycles. This research uses quantitative and qualitative methods. Data collected by questionnaire and interview techniques. The respondents in this research are 100 people who fulfill in one of five criteria; initiating, influencing, decision making, buying, and using Honda motorcycles in the district of mapanget. Two hypotheses are formulated and tested using Regression Analysis. The result shows that consumers motivation, and consumer attitudes have significant relationship with buying decision. Consumer motivation has higher influences for buying decisions than consumer attitudes. Keywords: Buying Decision, Consumer Motivation, Consumer Attitudes.